2012
DOI: 10.1111/j.1365-2427.2012.02820.x
|View full text |Cite
|
Sign up to set email alerts
|

Migratory benthic fishes may induce regime shifts in a tropical floodplain pond

Abstract: Summary 1. Alternative states are a widely recorded phenomenon in shallow lakes, which may shift between turbid‐ and clear‐water conditions. Here, we investigate whether such shifts in a tropical floodplain pond may be related to the effect of the flood pulse regime on the community structures of fish and macrophytes. 2. Using a long‐term data set, we demonstrate how benthic fish migration together with colonisation by submerged plants affected the transition from a turbid to a macrophyte‐dominated state in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 45 publications
1
36
0
2
Order By: Relevance
“…It has been suggested that factors affecting the timing and fraction of resident-migratory zooplanktivorous fish may provide feedback loops affecting the resilience of alternative stable states (macrophyte-dominated versus phytoplankton-dominated) in shallow eutropic lakes (Brönmark et al 2010). Furthermore, a recent study on migration in tropical floodplains suggested that migration of benthivorous fish drove the presence and absence of submerged macrophytes because of differences in resuspension affecting turbidity and thus light availability (Mormul et al 2012).…”
Section: Food-chain Effectsmentioning
confidence: 99%
“…It has been suggested that factors affecting the timing and fraction of resident-migratory zooplanktivorous fish may provide feedback loops affecting the resilience of alternative stable states (macrophyte-dominated versus phytoplankton-dominated) in shallow eutropic lakes (Brönmark et al 2010). Furthermore, a recent study on migration in tropical floodplains suggested that migration of benthivorous fish drove the presence and absence of submerged macrophytes because of differences in resuspension affecting turbidity and thus light availability (Mormul et al 2012).…”
Section: Food-chain Effectsmentioning
confidence: 99%
“…The low values of total phosphorous and nitrogen and the high values of Secchi disk depth observed in those sites closest to Porto Primavera dam are in accordance to the general trend observed worldwide, indicating that Porto Primavera dam is indeed acting as a sink of environmental nutrients. As observed by Thomaz et al (2009) and Mormul et al (2012) an alarming issue of the observed oligotrophication process, is that, by promoting increases in the water transparency, submerged aquatic macrophytes are able to develop and alter the planktonic community and also to facilitate the introduction of visual predators that will compete and predate native species (Fugi et al, 2008;Pereira et al, 2015), producing cascade effects on the trophic food webs (Harris et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The supply of plant propagules by river flooding waters and the subsequent desiccation and decomposition of macrophytes during falling waters were some mechanisms suggested to explain the observed shift (Loverde-Oliveira et al 2009). Flood dynamics controlled the migration of benthic fish, driving state shifts in a tropical floodplain pond (Mormul et al 2012). Increased turbidity during low waters was caused by sediment resuspension by fish and water clarity was enhanced at high waters, when fish migrated and submerged macrophytes expanded (Mormul et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Flood dynamics controlled the migration of benthic fish, driving state shifts in a tropical floodplain pond (Mormul et al 2012). Increased turbidity during low waters was caused by sediment resuspension by fish and water clarity was enhanced at high waters, when fish migrated and submerged macrophytes expanded (Mormul et al 2012). Besides, extreme water level variations can trigger the change from free-floating plant (FFP) dominance at high waters to a turbid regime with cyanobacteria dominance at low waters .…”
Section: Introductionmentioning
confidence: 99%